Estimating the interior layout of buildings using a shape grammar to capture building style - Yue, K.; Krishnamurti, R.; Grobler, Francois (American Society of Civil Engineering, 2012)
An algorithm is described for determining the interior layout of a building given three pieces of information: (1):the footprint of each story; (2):a reasonably complete set of exterior features; and (3):a shape grammar that describes the building style. Essentially, the algorithm prunes a layout tree generated by interpreting the shape grammar with constraints extracted from the footprint and exterior features. The Queen Anne house, commonly located in Pittsburgh, is chosen as the exemplars of the building style. It is shown how a shape-grammar interpreter for the Queen Anne house was developed and applied to the preceding problem. This shape-grammar interpreter provides the basis for developing grammar interpreters for general parametric shapes. For the purposes of illustration and comparison, applications of the approach to two other distinct building styles are briefly described. © 2012 American Society of Civil Engineers.